The landscape and challenges of postgraduate dental basic research education: a scoping review - Qianmin Ou; Deqian Tang; Shijie Chen; Zhuohong Gong; Manqing Liu; Xuejing Gan; Gengbin Cai; Xiaolan Li; Xuebin B. Yang; Yun Hong; Zetao Chen (BMC Oral Health)
Abstract Background Scientific research plays an important role in the advancement of dentistry. Postgraduate Dental Basic Research Education (PDBRE) is essential for enhancing the research knowledge and skills of research-focused students. This scoping review aims to identify the landscape and challenges of PDBRE, while also proposing future directions to further strengthen and optimize its effectiveness. Methods The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Extension for Scoping Reviews and followed a descriptive approach based on Arksey and O’Malley’s framework. A systematic search was conducted across PubMed, Web of Science, Embase, and the Education Resources Information Center (ERIC) databases to identify relevant literature up to May 20, 2024. Results The review screened 660 publications and selected 10 articles based on strict inclusion and exclusion criteria. These articles focused on curriculum contents, teaching methodologies, assessments, outcomes, and challenges related to effective research education in PDBRE. Conclusions PDBRE can enhance research-focused students’ foundational scientific research abilities by diversifying the curriculum content and teaching methodologies. However, challenges such as resource constraints, faculty shortages, workload, and student engagement hinder its development. To address these issues, we suggest strengthening faculty expertise and student involvement, alongside implementing a more systematic curriculum and improved assessment tools. Clinical trial number Not applicable.